Yearbook of the European Convention on Human Rights/Annuaire de la convention europeenne des droits de l'homme, Volume 34A : Freedom of Association / Liberté d'association (Human Rights and Humanitarian Law - Book Archive pre-2000., 1994)
The seminar on `Freedom of Association' was held in Reykjavik (Iceland) from 26 to 28 August 1993. It was organised by the Directorate of Human Rights of the Council of Europe in cooperation with the Ministry of Justice of Iceland, and dealt with the following four themes: freedom of association and political democracy; freedom of association and civil society; freedom of association and social democracy; freedom to form and join or not to join trade unions. Written communications were presented on the following subjects: case law of Article 11 of the European Convention on Human Rights, freedom of association and the freedom of associations, freedom of association of immigrants in Europe, freedom of association and public service and freedom of association, labour law and the needs of a democratic society. About one hundred personalities took part: representatives of governments of member States, representatives of non-governmental organisations, members of the European Commission and Court of Human Rights, professors and other interested persons from Central, Western and Eastern Europe competent in the fields covered by the themes of the Seminar. This publication contains the Proceedings of the Seminar: the official speeches made at the opening ceremony, the reports and written communications, the interventions, the final report and the list of participants. Le Séminaire sur la `Liberté d'association' a eu lieu à Reykjavik (Islande) du 26 au 28 août 1993. Il a été organisé par la Direction des Droits de l'Homme du Conseil de l'Europe en collaboration avec le Ministère de la Justice de l'Islande. Les travaux du Séminaire de Reykjavik ont été axés sur les quatre thèmes suivants: liberté d'association et démocratie politique; liberté des associations et société civile; liberté d'association et démocratie sociale; liberté de fonder avec d'autres des syndicats et de s'y affilier. Des communications écrites ont été présentées sur les questions suivantes: jurisprudence de l'Article 11 de la Convention européenne des Droits de l'Homme, liberté d'association et libertés des associations, liberté d'association des immigrés en Europe, liberté d'association et fonction publique et liberté d'association, droit du travail et les besoins d'une société démocratique. Une centaine de personnalités y ont participé: représentants de gouvernements des pays membres et d'organisations non gouvernementales, membres de la Commission et de la Cour européennes des Droits de l'Homme, personnalités du monde académique et autres personnalités de l'Europe occidentale, centrale et orientale compétentes dans les secteurs concernés par les thèmes du Séminaire. La présente publication contient les actes du Séminaire: les allocutions officielles faites lors de la cérémonie d'ouverture, les rapports et communications écrites présentés, les interventions, le rapport final et la liste des participants.